2013
DOI: 10.1371/journal.pone.0069147
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Human Gaucher Disease Gene GBA Generates Neurodevelopmental Defects and ER Stress in Drosophila Eye

Abstract: Gaucher disease (GD) is the most common of the lysosomal storage disorders and is caused by defects in the GBA gene encoding glucocerebrosidase (GlcCerase). The accumulation of its substrate, glucocylceramide (GlcCer) is considered the main cause of GD. We found here that the expression of human mutated GlcCerase gene (hGBA) that is associated with neuronopathy in GD patients causes neurodevelopmental defects in Drosophila eyes. The data indicate that endoplasmic reticulum (ER) stress was elevated in Drosophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 34 publications
(43 reference statements)
4
37
0
1
Order By: Relevance
“…In addition to NCSCs, α-synuclein accumulation has been reduced by ambroxol in SH-SY5Y overexpressing cell lines and transgenic SNCA/SNCA mice (McNeill et al, 2014;. In Drosophila fly models ambroxol reversed GBA mutant effects, including ER stress, reduced GCase activity and motor defects (Maor et al, 2016;Sanchez-Martinez et al, 2016;Suzuki et al, 2013). Transgenic mice carrying the L444P/+ gene and wild-type mice also had increased GCase activity in response to ambroxol (Luan et al, 2013;, the same was observed recently in healthy nonhuman primates (Migdalska-Richards et al, 2017).…”
Section: Administration Of Small Molecular Chaperones Have Been Reporsupporting
confidence: 68%
“…In addition to NCSCs, α-synuclein accumulation has been reduced by ambroxol in SH-SY5Y overexpressing cell lines and transgenic SNCA/SNCA mice (McNeill et al, 2014;. In Drosophila fly models ambroxol reversed GBA mutant effects, including ER stress, reduced GCase activity and motor defects (Maor et al, 2016;Sanchez-Martinez et al, 2016;Suzuki et al, 2013). Transgenic mice carrying the L444P/+ gene and wild-type mice also had increased GCase activity in response to ambroxol (Luan et al, 2013;, the same was observed recently in healthy nonhuman primates (Migdalska-Richards et al, 2017).…”
Section: Administration Of Small Molecular Chaperones Have Been Reporsupporting
confidence: 68%
“…Increased release of calcium from the ER has also been observed in iPS‐derived neurons or fibroblasts from patients with GBA mutations and PD. Drosophila models expressing PD‐associated GBA mutations have also exhibited activation of the UPR . Drosophila does not have a homologue of α‐synuclein, and therefore the loss of dopaminergic neurons and locomotor defects were independent of α‐synuclein pathology.…”
Section: Er Stress Mitochondrial Dysfunction and Neuroinflammationmentioning
confidence: 99%
“…In Drosophila , both ambroxol and isofagomine have been shown to effectively reduce the ER stress induced by mutant human GBA and also reverse the locomotor deficit observed in these models .…”
Section: Therapy For Gcase Deficiency In Pdmentioning
confidence: 99%
“…Takahiro Suzuki (currently, Shigray Inc.), who was a graduate student ( the University of Tsukuba) in Ishida Group of Clock Gene, AIST, succeeded in creating a model animal by transforming a variant human Gaucher disease gene in a Drosophila compound eye. [37] Gaucher disease is a lysosome disease Term 14 that is specified as one of diseases in the Research on Measures for Intractable Diseases Project of the Ministry of Health, Labour and Welfare. Due to a genetic mutation, the activity of enzymes called glucocerebrosidase is lost before birth.…”
Section: Essence Of Dementia Learned From Drosophila Geneticsmentioning
confidence: 99%